Ultrastructure and phylogeny of Ceratomyxa auratae n. sp. (Myxosporea: Ceratomyxidae), a parasite infecting the gilthead seabream Sparus aurata (Teleostei: Sparidae). Issue 5 (October 2015) - Rocha, Sónia; Casal, Graça; Rangel, Luís; Castro, Ricardo; Severino, Ricardo; Azevedo, Carlos; Santos, Maria João
Abstract A new myxosporean parasite is described from the gall bladder of the gilthead seabream Sparus aurata in a Southern Portuguese fish farm, with basis on light and transmission electron microscopy, as well as in molecular procedures. In the bile, young and mature mono- to disporic plasmodia were elliptical and presented smooth surface membranes. Crescent-shaped myxospores measured 6.7 ± 0.7 (5.3–7.6) μm in length and 27.0 ± 3.0 (19.7–31.2) μm in thickness. The myxospore wall was constituted by two symmetrical valves united along a slightly curved suture line, each presenting a lateral projection with a rounded end. Two equal-sized subspherical polar capsules, measuring 3.6 ± 0.2 (2.9–3.8) μm in length and 3.5 ± 0.3 (2.9–3.8) μm in width, were located at the same level, each displaying a polar filament coiled in 5 turns. Molecular analysis of the SSU rRNA gene confirmed the parasite as a new member of the genus Ceratomyxa, making this the fourth report of Ceratomyxa from the gall bladder of S. aurata in the Iberian Peninsula. This reinforces the assumption that species richness of ceratomyxids in South European sparids is high, but the phylogenetic analysis performed disagrees with the existence of a common ancestor for Ceratomyxa species infecting sparid hosts, as well as their clustering according to geographical location. The main Ceratomyxa clade is not monophyletic due to the inclusion of Palliatus indecorus and Pseudoalatospora kovalevae; a situation that will probably be resolved by the taxonomic revision of these genera.